Suppression of Neuroinflammation Attenuates Persistent Cognitive and Neurogenic Deficits in a Rat Model of Cardiopulmonary Bypass - Wang, Yi; Machizawa, Maro G.; Lisle, Turner; Williams, Cedric L.; Clarke, Ryon; Anzivino, Matthew; Kron, Irving; Lee, Kevin S. (Frontiers in Cellular Neuroscience, 2022)
Post-operative cognitive dysfunction (POCD) can be a serious surgical complication, and patients undergoing cardiac procedures are at particular risk for POCD. This study examined the effect of blocking neuroinflammation on behavioral and neurogenic deficits produced in a rat model of cardiopulmonary bypass (CPB). Minocycline, a drug with established anti-inflammatory activity, or saline was administered daily for 30 days post-CPB. Treatment with minocycline reduced the number of activated microglia/macrophages observed in the dentate gyrus of the hippocampus at 6 months post-CPB, consistent with an anti-inflammatory action in this CPB model. Behavioral testing was conducted at 6 months post-CPB utilizing a win-shift task on an 8-arm radial maze. Minocycline-treated animals performed significantly better than saline-treated animals on this task after CPB. In addition, the CPB-induced reduction in adult neurogenesis was attenuated in the minocycline-treated animals. Together, these findings indicate that suppressing neuroinflammation during the early post-surgical phase can limit long-term deficits in both behavioral and neurogenic outcomes after CPB.